Optimalisasi Branding Dan Re-Branding Produk UMKM Di Kelurahan Rungkut Tengah, Kecamatan Gunung Anyar, Kota Surabaya - Sheila Sabina Adelia Rizka; Ety Dwi Susanti (Jurnal Insan Pengabdian Indonesia, 2023)
Digitizing MSMEs is a program that is a solution for the government to improve the performance of MSMEs in the midst of intense business competition in the digital era. One example of digitizing MSMEs is the use of social media. The use of social media as a tool in a product marketing strategy needs to have a good brand image for consumers. Forming a good brand image can be done with a branding or re-branding strategy. Rungkut Tengah Village, Gunung Anyar District, Surabaya City is a place for MBKM KKN-T students to do their service to help MSME players in Rungkut Tengah Village who have problems in developing their businesses. Therefore, the purpose of this community service activity is to form a strategy to increase sales of MSME products through branding or re-branding strategies. The type of method used is qualitative by collecting data through observation, interviews and discussions with MSME actors. The result of this community service activity is that the development of MSMEs through product branding and re-branding strategies is going well.